In Vitro α-Glucosidase Inhibitory Activity of Ethanol Extract of Buas-buas (Premna serratifolia Linn) - Dini Hadiarti (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
In 2008, diabetics in Indonesia has reached 8,5 million of 11,1 % prevalence in West Kalimantan. It was estimated to reach 14,1 million in 2035. The treatment of diabetes may occur adverse reactions such as hypoglycemia, lipoatrophy, lipohypertrophy, lactic acidosis, gastrointestinal disturbances, allergic reactions, and obesity. Therefore, it is necessary to find an alternative medicine to overcome this problem. Buas-buas (Premna serratifolia Linn) could supposedly be an anti diabetic by inhibiting the α-glucosidase enzyme, due to the compositions of secondary metabolites, cardioprotective activity and it has a similar genus with Premna serratifolia Linn. The soxhlet extraction result from Premna serrtifolia Linn leaf powders produced of 34,1 % yield. Meanwhile, the activity of α-glucosidase in vitroinhibition test with amicroplate reader in various concentrations of samples of 0,125, 0,5, 1, 1,5, 2, dan 2,5 2% (b/v) were obtained the absorptions of 37,95, 74,77, 86,15, 91,03 and 91,69 %, respectively. The extraction of Premna serratifolia Linn leaf revealed that the concentration of 2 % of sample inhibited in vitro α-glucosidase with a percentage of 91,03 %. The extraction of Premna serratifolia Linn leafinhibited α-glucosidase of 97 % from the percentage of Acarboseinhibition.